Kualitas Laba, Growth Opportunity, Financial Distress, dan Nilai Perusahaan Industrial - Gusti Sultan Hakim; Angga Permadi Karpriana (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study examines the effect of earnings quality, growth opportunity, and financial distress on firm value in industrial sector companies listed on the Indonesia Stock Exchange during 2021-2025. Method: The study uses a quantitative approach with secondary data from annual reports, financial statements, stock prices, and other market information. The sample was selected using purposive sampling and produced 143 final observations after eliminating extreme data. Data were analyzed using multiple linear regression with IBM SPSS Statistics 23. Finding: The results show that earnings quality has no significant effect on firm value, while growth opportunity and financial distress measured using Altman Z-Score have positive and significant effects. Novelty: This study provides novelty by examining earnings quality, growth opportunity, and financial distress in one model using industrial sector companies listed on the Indonesia Stock Exchange during 2021–2025, a period that reflects post-pandemic business conditions and recent market dynamics.